Ship graffiti at the Zanzibar Gereza (Old Fort), Stone Town, Unguja, Tanzania. Issue 1 (2nd January 2022) - Cooper, John P.; Ghidoni, Alessandro
ABSTRACT: A number of graffiti of ships are to be found engraved into the plaster of the Gereza (Old Fort) of Stone Town on Unguja, the main island of the Zanzibar Archipelago, Tanzania. Most of those reported here appear on the ramparts of the southwestern tower, while some are on the western face of the main partition wall separating the western and eastern wards. Although sometimes sketchy, the images suggest a number of vessel types, including a frigate or frigate-built vessel and a number of settee-rigged ocean-going vessels referred to exonymically as 'dhows'. Some appear to have transom sterns, hinting at particular vessel types, such as the baghla, ghanja, sanbūq or kotia . Two graffiti might also depict the stem heads of the East African mtepe . The graffiti are documented and interpreted in the context of the fort, Oman's East African empire, and the Indian Ocean dhow trade. The construction history of the building and the vessel types depicted date the graffiti to the mid-late nineteenth century.